Association between hypertension and oxidative balance score: data from National Health and Nutrition Examination Survey 2005–2018 - Tao, Linfeng; Zhou, Yanyou; Wu, Lifang; Zhu, Yue; Li, Juntu; Li, Chao; Pan, Yiyuan; Liu, Jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertension, a prevalent worldwide public health issue, can result in a wide range of illnesses. The notably association between oxidative stress and the onset of hypertension has been corroborated through diverse animal models. The oxidative balance score (OBS) served as a tool to evaluate the overall systemic status of oxidative stress, indicating that higher OBS scores corresponded to greater exposure to antioxidants. However, the exact correlation between OBS and hypertension is unclear. Therefore, we aimed to investigate whether adult OBS is attached to hypertension.MethodsThere are 28,035 participants who were chosen from the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2018. The presence of hypertension was determined through a questionnaire. Twenty food and lifestyle parameters were used to score OBS. The connection between OBS and hypertension has been examined via weighted logistic regression and smoothing curves.ResultsThe percentage of people with hypertension stood at 41.72%. In comparison to the first quartile of OBS, the adjusted odds ratios for the highest OBS quartile and hypertension were 0.81 (95% CI: 0.70–0.93), with a p-value for trend of 0.002. Age was the factor most strongly linked with both in stratified analysis.ConclusionsOBS demonstrated a strong negative association with hypertension, particularly in the younger population (<60 years). These findings highlighted the importance of following an antioxidant-rich diet and lifestyle, which aids in hypertension prevention and appears to offer greater benefits to the younger age group.